(untitled) (MAUSAM, 1980)
The paper presents an attempt to develop a numerical model for flood routing. This has been done for the river Yamuna. Using an implicit difference scheme, we present results to show that the model predicts the discharge and time of arrival of the peak flood with reasonable accuracy.